A conceptual framework of the influence of packaging design on purchase intention / Roszi Naszariah Nasni Naseri … [et al.] - Naseri, Roszi Naszariah Nasni; Mohd Esa, Maryam; Yahya, Wan Kalthom; Muthusamy, Geetha; Ibrahim, Roslinawati; Jais, Zurairah (Faculty of Art and Design, 2024)
The objective of this study is to provide an understanding of the influence of packaging design on consumer purchase intentions through the presentation of a conceptual framework. The proposed conceptual framework incorporates fundamental principles derived from the Stimulus-Organism-Response (SOR) model and the Theory of Planned Behavior (TPB). This analysis explores the impact of external cues, particularly packaging design, on customers' cognitive and affective reactions (Organism), ultimately influencing their intentions to make a purchase (Response). The elements of the Theory of Planned Behavior (TPB), including Attitudes, Subjective Norms, and Perceived Behavioural Control, serve as intermediary variables within the organism component of the Social Organisational Relations (SOR) model. It is important to incorporate both exterior cues and internal psychological aspects when studying consumer behaviour, as this integration provides vital insights into the psychological processes that influence customer purchase intentions.